ANALISIS PENGGUNAAN SISTEM ELEKTRONIK PAJAK TERHADAP PENINGKATAN JUMLAH WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA - AKBAR NISTAH TARAFATUR, VICKY (Jurnal Akuntansi AKUNESA, 2013)
The use of electronic system reduces the practice of collusion or bribery in DJP. It isnot necessary that the taxpayers come to DJP. Also, the data can be more organized and thecounting process will be done fast as it is computerized. This research is a descriptiveresearch, which is done to find the effects of electronic tax system on the number of taxpayersat KPP Pratama Surabaya-Gubeng. Empirically, since the electronic system was firstlaunched, there is quite a significant rise in the number of taxpayers at KPP PratamaSurabaya-Gubeng, from 624 in 2006 to 3.486 in 2007.Key Words: Electronic tax system, Taxpayers